AB0907 Treatment patterns in psoriatic arthritis in us and europe: results from a real-world international survey. (12th June 2018) - Orbai, A.-M.; Gossec, L.; Lobosco, S.; Moon, R.; Massey, O.; Piercy, J.; Cappelleri, J.C.; Fallon, L.; Young, P.; Romero, A.B.; Hsu, M.-A.
Abstract : Background: With the availability of a greater range of Psoriatic Arthritis (PsA) treatment options, it is increasingly necessary to understand their use and impact on disease control in real-world practice. Objectives: To assess treatment patterns and their impact on clinical outcomes among PsA patients currently receiving conventional/targeted synthetic disease-modifying anti-rheumatic drugs (cs/tsDMARD) or biologic DMARD (bDMARD). Methods: A point in time survey was conducted in 2015 across the US, France, Germany, Italy, Spain and UK. Patients had physician-confirmed PsA and had to have been receiving their current cs/tsDMARD (bio naïve) or bDMARD (1st or 2nd line) for ≥6 months. Physicians provided information on demographics, treatment history, disease severity, clinical measures included body surface area (BSA), joint count, flare/remission status. Student t-tests, Pearson's chi-squared and Fisher's exact tests were used to compare physician-reported patient profile variables, clinical status and treatment outcomes. Results: 519 physicians (331 rheums, 188 derms) provided data for 2467 PsA patients, 1463 of whom met the inclusion criteria (1136 EU, 327 US). No significant differences were observed between EU and US patients in demographics (male 52.6%, mean age 49.0 years), disease duration 6.3 years; disease severity 29.1% moderate to severe). In the EU, 32.3% patients were on cs/tsDMARDs, 55.4% 1st-line bDMARD, 12.3% 2nd-line bDMARD vs 21.7%, 58.4%, 19.9% respectively in the US. Time in months (mo) from diagnosis to first cs/tsDMARD was similar in the EU and US (EU mean 4.7 mo; US 8.1 mo, p=0.24), from 1st cs/tsDMARD to 1st bio (EU 37.4 mo; US 29.4 mo, p=0.15). Patients in the EU received more cs/tsDMARDs prior to bDMARD initiation than US patients (mean 1.4 v 0.8; p<0.001). US patients were more likely to have bDMARD without combination cs/tsDMARDs (US 65.1% vs EU 52.3%; p=0.004). Patients receiving cs/tsDMARDs had a worse clinical profile than those on 1st-line bDMARD in all areas other than joint count. Patients on 2nd-line bDMARD had more symptoms, more affected joints and more likely to flare vs 1st-line bDMARD. They had more affected joints but were less likely to flare vs cs/tsDMARD. These findings were directionally similar in the EU and US (table 1). BSA was higher for cs/tsDMARD patients than for any bDMARD patients. Conclusions: Only 39%–60% of patients were considered by physicians as in remission, revealing a considerable unmet need in both the EU and US in patients treated with cs/tsDMARDs and bDMARDs. Further research is needed to identify patients on cs/tsDMARDs who may be a candidate for advanced therapy and to recognise patients who might fail on bDMARD who therefore may benefit from a different therapeutic alternative. Disclosure of Interest: A.-M. Orbai Grant/research support from: AbbVie, Celgene, Eli Lilly, Horizon, Janssen, Novartis, Pfizer, Consultant for: Eli Lilly, Janssen, Novartis, Pfizer, UCB, L. Gossec Grant/research support from: UCB, Lilly, Pfizer, BMS, Consultant for: AbbVie, BMS, Celgene, Janssen, Novartis, Pfizer, Roche UCB, S. Lobosco Employee of: Adelphi Real World, R. Moon Employee of: Adelphi Real World, O. Massey Employee of: Adelphi Real World, J. Piercy Employee of: Adelphi Real World, J. Cappelleri Shareholder of: Pfizer, Employee of: Pfizer, L. Fallon Shareholder of: Pfizer, Employee of: Pfizer, P. Young Employee of: Pfizer, A. Romero Employee of: Pfizer, M.-A. Hsu Shareholder of: Pfizer, Employee of: Pfizer